Analisis Penambahan Pre Filter Terhadap Penurunan Tekanan Dan Endapan Pada Filter Berbahan Bakar Campuran Diesel Biodiesel - Negara, I Gede Bangsa; Ghurri, Ainul; Wirawan, I Ketut Gede (Teknik Desain Mekanika; Vol 10 No 4 (2022): Oktober 2022 : Teknik Desain Mekanika, 2022)
Abstract Biodiesel is an alternative fuel that can replace diesel oil as diesel engine fuel. The use of biodiesel will affect the diesel engine components, one of the component is the fuel filter where the filtered dirt will form sediments so that the fuel filter will be clogged faster. A clogged fuel filter will cause a pressure drop in the fuel flow which causes the fuel flow to be imperfectly distributed into the engine. The purpose of this study is to examine the effect of variations in the mixture of diesel oil and biodiesel on the pressure drop and sediment on the fuel filter. This experiment is carried out with 400 liters of fuel flowing through the fuel filter by varying the mixture of Pertamina Dex B20 diesel oil, Pertamina Dex B30, Dexlite and additional pre filters. The initial fuel pressure is set at 105 kPa before entering the fuel filter. The test results show that the variation of the mixture of diesel oil and biodiesel has an effect on the blockage of the fuel filter. The more biodiesel content, the easier it is for the fuel filter to clog. The Pertamina Dex B30 test showed the highest pressure drop was 55 Kpa and the sediment that occurred was 163.84 grams for the main filter and 203.19 grams for the pre filter. Keywords: Diesel-Biodiesel blend, Fuel Filter, Pre Filter, Pressure Drop, Sediment